Monolayer–Trilayer Lateral Heterostructure Based Antimonene Field Effect Transistor: Better Contact and High On/Off Ratios. Issue 5 (24th March 2018) - Chen, Jianyong; Yang, Zhixiong; Zhou, Wenzhe; Zou, Hui; Li, Mingjun; Ouyang, Fangping
Abstract : Inspired by the unique character of the semiconductor‐to‐metal transition from monolayer to trilayer antimonene, we built a monolayer–trilayer lateral heterostructure based field effect transistor (FET). Low tunneling barrier and Schottky barrier are achieved with trilayer antimonene electrodes compared with promising two‐dimensional contact material graphene and metal aluminum. Device performance is calculated accurately using the density functional theory (DFT) and nonequilibrium Green's functions (NEGF). The on/off ratio is 4.87 × 10 8 with the gate length 10.0 nm. Even if the gate length decreases to 5.0 nm, the on/off ratio is still as high as 1.06 × 10 6 . The lowest power supply voltage ( V dd = 0.76 V) at V ds = 0.6 V to switch "on" and "off" is very close to the requirement of 0.72 V. In addition, the on‐current can be enhanced by a factor of six and on/off ratio is simultaneously lifted up through hydrogen passivation, which offers a route to further optimize the device performance. Low off‐current and high on/off current ratio along with high air stability make the monolayer–trilayer lateral heterostructure based antimonene FET a potential candidate for future low power device applications. Abstract : A unique field effect transistor composed of monolayer antimonene as channel and trilayer antimonene as electrodes is investigated. Low tunneling barrier and Schottky barrier are achieved. The on/off ratio and power supply voltage can satisfy the low power performance requirements of the International Technology Roadmap for Semiconductors in the next decade. Furthermore, the on‐current rises sixfold through hydrogen passivation.